Anti-oxidative stress mechanism of cyclic dipeptide in distiller's grains of strong-flavor Baijiu - GUO Yan, LIAO Qinjian, ZHENG Jia, WANG Fang, YANG Hao, ZHOU Hanling, SU Jian (Zhongguo niangzao, 2025)
In this study, the in vitro antioxidant activity of free peptides in distiller's grains of strong-flavor (Nongxiangxing) Baijiu was determined by measuring the free radical scavenging rate of 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH). The cyclic peptides in the free peptides were identified using high performance liquid chromatography-quadrupole-time of flight tandem mass spectrometry (HPLC-Q-TOF-MS), and the anti-oxidative stress action mechanism of cyclic peptides was studied using network pharmacology combined with molecular docking methods. The results showed that the content of cyclic dipeptides in distiller's grains was 30.20 mg/g, and the half maximal inhibitory concentration (IC50) value of DPPH radicals was 2.30 mg/ml, which had a certain in vitro antioxidant capacity. A total of 19 cyclic peptides were isolated and identified from the distiller's grains extract, including 10 cyclic dipeptides, 2 cyclic tripeptides, 7 cyclic peptide ethyl esters. Among them, 8 cyclic dipeptides were involved in 274 core targets related to antioxidant effects, including 8 key core targets. All 8 cyclic dipeptides and 8 key core targets could form stable complexes through intermolecular forces, and exerted anti-oxidative stress effects through multi-target and multi-pathway, mainly involved in apoptosis, cancer, calcium regulation, inflammation and other biological processes.